"I Will Tell You a Story about Jihad": ISIS's Propaganda and Narrative Advertising. (26th July 2020) - Kruglova, Anna
Abstract: This article further broadens the understanding of ISIS propaganda and its effectiveness by looking at the group's social media through the prism of marketing. The group was found to rely on a narrative type of advertising while creating its propaganda. Specifically, ISIS was using stories to appeal to its recruits' emotions and desires. The use of stories helped ISIS to establish a strong connection with its target audience, and increased the group's success in promoting its ideas.